On the Political Feasibility of Increasing the Legal Retirement Age - Benjamin Bittschi; Berthold U. Wigger (Center for Economic Studies and ifo Institute (CESifo), 2019)
Within a politico-economic model we first establish three hypotheses: (i) Retirees generally prefer a higher retirement age than workers, whereby just retired individuals prefer the highest retirement age, (ii) in equilibrium the level of the legal retirement age is increasing in longevity and (iii) decreasing in the public pension replacement rate. We then test these hypotheses empirically. Employing micro data for Germany we corroborate the first hypothesis with descriptive regressions and a fuzzy regression discontinuity (FRD) design. We show that just retired individuals are indeed most in favor of an increase in the legal retirement age. On the basis of cross country panel IV regressions we provide evidence for the second and third hypothesis. We demonstrate that a one percentage point increase in the share of the elderly increases the legal retirement age by 0.3 to 0.5 years, and that a 10 percentage point increase in the replacement rate reduces the legal retirement age by 0.5 to 3 years. We conclude that if policy contains the generosity of public pensions, increasing the legal retirement age becomes politically more feasible.
Keywords: D72; H55; J26; 330; retirement age; pension reform; longevity; replacement rate